Crystal structure of bis(acetylacetonato)bis(quinoline)nickel(II), Ni(C5H14O2N)2 (C9H7N)2 - Zukerman-Schpector, J.; Caracelli, I. [UNESP]; Trindade, A. C.; Cussigh, O.; Dunstan, P. O. (De Gruyter, 2006)
C28H28N2NiO4, triclinic, PI (no. 2), a = 7.9202(6) Å, b = 8.0496(6) A, c = 10.246(1) Å, a = 97.15(1)°, β = 106.68(1)°, γ = 94.686(9)°, V= 616.1 Å3, Z = 1, Rgt(F) = 0.028, wRref(F2) = 0.078, T = 293 K.